2007
DOI: 10.1093/brain/awm248
|View full text |Cite
|
Sign up to set email alerts
|

Chloride channel myotonia: exon 8 hot-spot for dominant-negative interactions

Abstract: Myotonia congenita (MC) is the commonest genetic skeletal muscle ion channelopathy. It is caused by mutations in CLCN1 on chromosome 7q35, which alter the function of the major skeletal muscle voltage-gated chloride channel. Dominant and recessive forms of the disease exist. We have undertaken a clinical, genetic and molecular expression study based upon a large cohort of over 300 UK patients. In an initial cohort of 22 families, we sequenced the DNA of the entire coding region of CLCN1 and identified 11 novel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
114
2
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 109 publications
(122 citation statements)
references
References 18 publications
4
114
2
2
Order By: Relevance
“…Patients with recessive myotonia congenita typically experience a peculiar transient weakness on initiating an action, which is only rarely seen in dominant myotonia congenita. Although Becker found that most patients with recessive myotonia congenita presented between the ages 4 and 12 years while the dominant form usually manifested before the age of 3 years (Becker, 1977), we found no difference in the age of onset (Fialho et al, 2007).…”
Section: Clinical Features Myotonia Congenitacontrasting
confidence: 77%
See 3 more Smart Citations
“…Patients with recessive myotonia congenita typically experience a peculiar transient weakness on initiating an action, which is only rarely seen in dominant myotonia congenita. Although Becker found that most patients with recessive myotonia congenita presented between the ages 4 and 12 years while the dominant form usually manifested before the age of 3 years (Becker, 1977), we found no difference in the age of onset (Fialho et al, 2007).…”
Section: Clinical Features Myotonia Congenitacontrasting
confidence: 77%
“…Some clinical findings are more common in the recessive than in the dominant form but considerable overlap exists. Recessive myotonia congenita tends to be more severe, is more frequently associated with muscle hypertrophy and with depressed tendon reflexes (Becker, 1977;Fialho et al, 2007). Patients with recessive myotonia congenita typically experience a peculiar transient weakness on initiating an action, which is only rarely seen in dominant myotonia congenita.…”
Section: Clinical Features Myotonia Congenitamentioning
confidence: 99%
See 2 more Smart Citations
“…2 Transient weakness, generalized muscle hypertrophy and depressed deep tendon reflexes were more common in recessive myotonia congenita. 2,3 The recessive form is believed to be caused by 2 loss-of-function mutations, whereas the dominant form is assumed to be a consequence of a dominant-negative effect. 4 CLCN1 is located on chromosome 7q35 and encompasses 35 kb in genomic DNA with 23 exons.…”
Section: Introductionmentioning
confidence: 99%